Emerging role of air pollution and meteorological parameters in COVID‐19. Issue 2 (18th May 2021) - Zhao, Channa; Fang, Xinyu; Feng, Yating; Fang, Xuehui; He, Jun; Pan, Haifeng
Abstract: Exposure to air pollutants has been associated with respiratory viral infections. Epidemiological studies have shown that air pollution exposure is related to increased cases of SARS‐COV‐2 infection and COVID‐19‐associated mortality. In addition, the changes of meteorological parameters have also been implicated in the occurrence and development of COVID‐19. However, the molecular mechanisms by which pollutant exposure and changes of meteorological parameters affects COVID‐19 remains unknown. This review summarizes the biology of COVID‐19 and the route of viral transmission, and elaborates on the relationship between air pollution and climate indicators and COVID‐19. Finally, we envisaged the potential roles of air pollution and meteorological parameters in COVID‐19.